Comparing the expectations of undergraduate and graduate degree students - POLAT, ZÜHAL (ELSEVIER SCIENCE BV, 2010)
The aim of this study is to determine the academic expectations and satisfaction levels of the Marmara University Technical Education Faculty (TEF) and the Technical Sciences Vocational School (TBMYO) students by analyzing comparatively. Research universe is the students at Marmara University, TEF, TBMYO. The data of the study is collected by using Student Profile Survey developed by the users. TEF and TBMYO students are considered comparatively and statistical analysis has been carried out. At the end of the study, it is concluded that the expectation levels of the students are high whereas the satisfaction levels are low. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: University education; academic quality; academic satisfaction; student expectations